Total-evidence phylogeny and divergence times of Vermilingua (Mammalia: Pilosa). Issue 3 (2nd April 2020) - Casali, Daniel de melo; Dos Santos Júnior, José EustáQuio; Miranda, Flávia Regina; Santos, Fabrício Rodrigues; Perini, Fernando Araújo
Abstract : Vermilingua is a peculiar group of xenarthran placental mammals with well-established phylogenetic relationships based on morphological and molecular data, but until now, no combined analysis of those data types. Here we perform the first total-evidence phylogenetic analysis of Vermilingua and estimate divergence times for living and fossil anteaters with a tip-dating approach, using the Fossilized Birth-Death model in a Bayesian framework. Using combined analyses, we recovered as monophyletic the two families, Cyclopedidae and Myrmecophagidae, as in previous studies, although our revised morphological data alone do not support the monophyly of Cyclopedidae. We show how the combination of molecular and morphological data indirectly affects the position and support for fossil taxa even though molecular datasets do not contain direct information for them. The estimated divergence times of Palaeomyrmidon and Protamandua are much older than the ages of those fossils, reinforcing the scarcity of the vermilinguan fossil record. In addition, we obtained evidence that the extinct Neotamandua is an ancestor of the extant Myrmecophaga, not a sister taxon as in previous studies, that did not incorporate the possibility of anagenetic evolution between fossil and living taxa.